The Effect of Quality of Work Life, Competence, Communication, Career Development, and Motivation on Employee Performance At PT. Bank BRI (Bank Rakyat Indonesia) Aek Nabara District - Mariana, Uci; Elvina, Elvina; Halim, Abd (Pusat P2M Politeknik Negeri Batam, 2025)
This study analyses the Influence of Quality of Work Life, Competence, Communication, Career Development, and Motivation on Employee Performance at PT. Bank BRI (Bank Rakyat Indonesia) Aek Nabara District. Data collection techniques used in the study were observation, documentation, and questionnaires using a Likert scale. The population in this study was 35 employees of PT. Bank BRI (Bank Rakyat Indonesia) Aek Nabara District. The entire population in this study will be used as a sample, namely 35 employees. The study's results prove that Quality of Work Life positively and significantly affects Employee Performance. Competence has a positive and significant effect on Employee Performance. Communication has a positive and significant effect on Employee Performance. Career Development has a positive and significant effect on Employee Performance. Motivation has a positive and significant effect on Employee Performance at PT. Bank BRI (Bank Rakyat Indonesia) Aek Nabara District.